'Please don't destroy until it's completely destroyed': Arts of education towards democracy. Issue 3 (25th August 2021) - Yun, SunInn
Abstract: The Black Lives Matter campaign has led many people around the world to reassess monuments that are installed in public spaces to commemorate historical figures. These reassessments raise questions about what it means to attack the statues of the past, what the rights and wrongs of such actions are, what this teaches us and how all this is passed on to the next generation. In line with this, I focus on a statue of the former dictator of Korea, Chun Doo‐hwan, installed in 2019. The purpose of the statue was, however, somewhat different from that of many other statues currently at issue. It was erected for the purpose of humiliation rather than respect. By examining the case of the statue of Chun Doo‐hwan in Korea, this paper discusses the nature of democracy in relation to these attacks on statues. In particular, it attempts to interpret the installation of the statue as a form of art for an emancipated community, where democracy is understood as involving a haunting of the collective memory. It concludes that democracy is something never to be grasped fully, something that slips away from its intentions and that is always to be tested and reconsidered. Finally, the paper addresses the educational significance of the statue in question in terms of how history is to be taught and how, in our interactions with the statues around us, the past is to be remembered.